Thoughts & notions - Lee, Linda (Heinle & Heinle,Trẻ, 2000)
Designed for high-beginning ESL learners, Thoughts & Notions is the second in a series of three reading texts which enables students to develop a useful and personally relevant vocabulary base while exploring and expanding their critical thinking skills